Investigações sobre números naturais e processos de ensino e aprendizagem desse tema no início da escolaridade - Bonaldo, Icléa Maria (2007)
This research has the objective to investigate the education and learning of natural numbers, searching to identify similarities and differences between the results and indications of research on the construction of numbers concepts for the children. It analyzes the contributions of Piaget, Kamii, Fayol, Lerner and Sadovsky and the implications that these researchs had brought and brings for the work in classroom, especially in the initial year of Basic School. We investigate how the lines of direction in official documents are translated in the practical of the teachers in classroom. We search to discover what a group of teachers, who act at the initial year, and what they know about the number construction idea and how it is worked in classroom. The questions of the research that guide our work are the following ones: which contributions for the construction of the concept of numbers by the children bring theories and research developed for authors as Piaget, Kamii, Fayol, Lerner and Sadovsky?; in curricular official documents these directions had been presented, throughout of last decades, regarding the process of education and learning of natural numbers by the children, at the beginning of basic education?; what knowledge about the subject can be identified in speech of a group of teachers searched and which conjectures we can formulate on their practice, analyzing some tasks used by them